2021
DOI: 10.1111/mec.15778
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific transcription patterns support the kinship theory of intragenomic conflict in honey bees (Apis mellifera)

Abstract: Kin selection may act differently on genes inherited from parents (matrigenes and patrigenes), resulting in intragenomic conflict. This conflict can be observed as differential expression of matrigenes and patrigenes, or parent‐specific gene expression (PSGE). In honey bees (Apis mellifera), intragenomic conflict is hypothesized to occur in multiple social contexts. Previously, we found that patrigene‐biased expression in reproductive tissues was associated with increased reproductive potential in worker honey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(47 citation statements)
references
References 45 publications
(69 reference statements)
4
42
1
Order By: Relevance
“…This study provides evidence for the role of intragenomic con ict in mediating aggression and colony defense in worker honey bees. When coupled with previous studies that demonstrated how intragenomic con ict shapes worker reproduction [17,19,21,22], our results suggest that intragenomic con ict and parent-speci c transcription may be important factors in shaping the individual variation seen within the context of social behavior in honey bees, and potentially other species [24,32]. We examined whether RNA m6A and/or alternative splicing play a role in intragenomic con ict in honey bees and did not nd evidence to suggest that either are associated with parent-speci c transcription in this species.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This study provides evidence for the role of intragenomic con ict in mediating aggression and colony defense in worker honey bees. When coupled with previous studies that demonstrated how intragenomic con ict shapes worker reproduction [17,19,21,22], our results suggest that intragenomic con ict and parent-speci c transcription may be important factors in shaping the individual variation seen within the context of social behavior in honey bees, and potentially other species [24,32]. We examined whether RNA m6A and/or alternative splicing play a role in intragenomic con ict in honey bees and did not nd evidence to suggest that either are associated with parent-speci c transcription in this species.…”
Section: Discussionmentioning
confidence: 65%
“…For each transcript, all positions were required to exhibit the same direction of parent-or lineage-speci c bias at previously established thresholds for p1 (the proportion of reads mapping to the AHB allele in offspring from the EHB queen and AHB drone cross) and p2 (the proportion of reads mapping to the AHB allele in offspring from the AHB queen and EHB drone cross) for the transcript to be reported as exhibiting bias. Additionally, a GLIMMIX [17,21,22] was t for each transcript, separately, to test for an effect of parent, lineage, and their interaction. Test results were FDR corrected, and only transcripts with a signi cant effect of parent or lineage, but not their interaction, were considered to exhibit bias.…”
Section: Generation Of Parental Transcriptomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals and plants, 'imprints' typically involve sexspecific DNA methylation of the promoter regions of the relevant genes [67,68]. In insects, parent-specific allele expression levels are repeatedly observed [69][70][71][72]. However, the underlying molecular mechanisms of the imprinting that cause parent-specific gene expression (PSGE) in insects have not been conclusively established [43].…”
Section: (B) Parent-specific Gene Expression and Genomic Imprintingmentioning
confidence: 99%
“…The function of DNA methylation in insects is largely unknown and thought to be variable based on the range of overall levels between taxonomic orders (Provataris et al ., 2018). However, multiple insect species have now been show to display parent-of-origin gene expression, including the mealybug Planococcus citri (de la Filia et al ., 2021) and two Hymenopteran species, the bumblebee, Bombus terrestris (Marshall et al ., 2020b) and the honeybee Apis mellifera (Kocher et al ., 2015; Galbraith et al ., 2016; Smith et al ., 2020; Galbraith et al ., 2021). In Hymenoptera, DNA methylation has been associated with caste differences in various species (Lyko et al ., 2010; Bonasio et al ., 2012; Amarasinghe et al ., 2014; Glastad et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%